A Moving Mesh Method for the Euler Flow Calculations Using a Directional Monitor Function (Communications in Computational Physics, 2006)
This paper is concerned with the adaptive grid method for computationsof the Euler equations in fluid dynamics. The new feature of the present moving meshalgorithm is the use of a dimensional-splitting type monitor function, which is to increasegrid concentration in regions containing shock waves and contact discontinuities or theirinteractions. Several two–dimensional flow problems are computed to demonstrate theeffectiveness of the present adaptive grid algorithm.